Shape-topology optimization for Navier–Stokes problem using variational level set method - Duan, Xian-Bao; Ma, Yi-Chen; Zhang, Rui (Journal of computational and applied mathematics, 2008)
We consider the shape-topology optimization of the Navier–Stokes problem. A new algorithm is proposed based on the variational level set method. By this algorithm, a relatively smooth evolution can be maintained without re-initialization and drastic topology change can be handled easily. Finally, the promising features of the proposed method are illustrated by two benchmark examples.